2023
DOI: 10.1038/s41522-023-00370-y
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial potential of known and novel probiotics on in vitro periodontitis biofilms

Abstract: Several oral diseases are characterized by a shift within the oral microbiome towards a pathogenic, dysbiotic composition. Broad-spectrum antimicrobials are often part of patient care. However, because of the rising antibiotic resistance, alternatives are increasingly desirable. Alternatively, supplying beneficial species through probiotics is increasingly showing favorable results. Unfortunately, these probiotics are rarely evaluated comparatively. In this study, the in vitro effects of three known and three … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Van Holm and colleagues also found that CFS from L. rhamnosus GG strongly killed P. gingivalis , while against F. nucleatum , L. reuteri F471 was more effective [ 26 ]. L. rhamnosus CT-53 inhibited F. nucleatum and P. gingivalis when used both as a viable strain in the agar overlay method, and heat-killed strain in the pathogen CFU counting after treatment [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Holm and colleagues also found that CFS from L. rhamnosus GG strongly killed P. gingivalis , while against F. nucleatum , L. reuteri F471 was more effective [ 26 ]. L. rhamnosus CT-53 inhibited F. nucleatum and P. gingivalis when used both as a viable strain in the agar overlay method, and heat-killed strain in the pathogen CFU counting after treatment [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Van Holm et al also observed that the presence of L. rhamnosus GG decreased the amount of F. nucleatum and P. gingivalis in their own biofilm [ 26 ]. L. reuteri AN417 CFS reduced the biofilm integrity of F. nucleatum and P. gingivalis , and also decreased the P. gingivalis expression of genes involved in biofilm formation [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, maintaining the oral microecological balance is of great importance to oral health in humans. Several studies have shown that probiotics may help to maintain oral microbiota homeostasis and improve oral health (Zhang et al, 2020b;Van Holm et al, 2023). Probiotics can colonize the oral cavity and replace certain pathogenic bacteria (Bonifait et al, 2009;Rossoni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics can colonize the oral cavity and replace certain pathogenic bacteria (Bonifait et al, 2009;Rossoni et al, 2018). They can produce antimicrobial substances (such as fatty acids, H 2 O 2 , and bacteriocins) to resist colonization by pathogenic bacteria (Yoon et al, 2018;Van Holm et al, 2023). Additionally, some probiotics may help to resist the development of low pH in the mouth (Meurman and Stamatova, 2007;Güngör et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, maintaining oral microecological balance is of great importance to human oral health. Several studies have shown that probiotics may help maintain oral microbiota homeostasis and improve oral health [9,15]. Probiotics can colonize the oral cavity and replace certain pathogenic bacteria [16,17].…”
Section: Introductionmentioning
confidence: 99%